Hipertensão arterial em adolescentes escolares de São José do Rio Preto: prevalência e fatores de risco - Santos, Antonio Augusto Cais dos (2004)
The actual prevalence of arterial hypertension in adolescents is still a matter of controversy, with rates ranging from 1% to 10%. In order to assess this prevalence and therisk factors for arterial hypertension, 5174 adolescents (13 to 18 years) attending public and private schools in a 350,000 inhabitant Brazilian city were screened. One week before the first visit, informed consent was signed and a questionaire to be answered by parents was given. In visit one, blood pressure, height and weight were measured at schools and the questionaire was collected. Blood pressure measurement was done following recommendations of the 1996 Update on the 1987 2nd Task Force Report on High Blood Pressurein Children and Adolescents. Adolescnets with blood pressure equal or above the percentile 95th for age, height and sex were refered for a second and third visit at the medical office. Adolescents with abnormal blood pressure at visit one and in only one more visit were considered as labile arterial hypertension and individuals with abnormal blood pressure in all three visits were considered hypertensive.There was 0,7% (35) of hypertensive adolescents (30 with sistolic hypertension and 5 with diastolic hypertension) and 1,4% (75) of labile hypertension. When the hypertensive population (age 15 ± 1 year) was comparedto the normal blood pressure adolescents (age 15 ± 2 years) a greater body mass index (29 ± 6 versus 21 ± 4, p< 0, 00001), a higher percent of body mass index above then normal (77% versus 13%, p<0,00001), a higher rate of males ( 80% versus 38%, p<0,0001) and a statistically higher rate of history of previous nephritic or nephrotic syndrome was found in hypertensive adolescents. There was a trend to low family income in hypertensive adolescents (20% versus 9,7%, p=0,076). There was no difference between birth weight (low than 2,500g), black race, salt consuption, sports practice and positive parents history for hypertension between the two groups. In conclusion, a methodologically adequate survey using a large sample found a smaller prevalence of hypertension in adolescents than previous studies. Hypertension was related to overweight and obesity, male gender, previous history of nephrotic or nephritic syndromes and likely to lower social economical level. The significant amount of labile hypertension reinforces the need for a careful evaluation before the diagnosis of hypertension can be made in adolescents.